Case Report: Artifactual Hypoglycemia: A Condition That Should Not Be Forgotten - Amaral, A (2022)
Background: Hypoglycemia is uncommon in people who are not being treated for diabetes mellitus and, when present, the differential diagnosis is broad. Artifactual hypoglycemia describes discrepancy between low capillary and normal plasma glucose levels regardless of symptoms and should be considered in patients with Raynaud's phenomenon. Case presentation: A 46-year-old female patient with a history of a sleeve gastrectomy started complaining about episodes of lipothymias preceded by sweating, nausea, and dizziness. During one of these episodes, a capillary blood glucose was obtained with a value of 24 mg/dl. She had multiple emergency admissions with low-capillary glycemia. An exhaustive investigation for possible causes of hypoglycemia was made for 18 months. The 72h fasting test was negative for hypoglycemia. A Raynaud's phenomenon was identified during one appointment. Conclusion: Artifactual hypoglycemia has been described in various conditions including Raynaud's phenomenon, peripheral arterial disease, Eisenmenger syndrome, acrocyanosis, or hypothermia. With this case report, we want to reinforce the importance of being aware of this diagnosis to prevent anxiety, unnecessary treatment, and diagnostic tests.